Turkey - Ozudogru, Osman; Yerlikaya, Emrah; Alayunt, Naci Omer; Ã‡ambay, Zafer (Jurnal Teknologi Laboratorium, 2021)
The purpose of this study is to investigate the healing effect of Favipiravir used in pre-intensive care treatment of patients diagnosed with COVID-19 in order to elucidate the pathogenesis and complications of coronavirus. The data regarding the clinical findings of the patients in the hospital information system and the biochemical parameters made standard in the treatment/follow-up of COVID 19 were taken from the system and evaluated retrospectively. In addition, it was examined as a whole with mild, moderate and severe pulmonary involvement compared to CT findings. Hemogram, coagulation and biochemistry parameters used in the diagnosis and follow-up of COVID-19 were evaluated. SPSS 22.0 statistics program for Windows was used in statistical analysis to evaluate the data obtained from patient files and hospital information system. There is no definitive treatment protocol within the scope of treatment. Drug studies are currently ongoing. In this study, the first clinical findings, treatment types and recovery times of patients diagnosed with COVID-19, the healing effect of favipiravir used before intensive care were determined. Between group 1 (those who started treatment within 0-5 days) and group 2 (those who started treatment within 6-10 days), after 5 days of favipravir treatment, when serum parameters were compared, favipravir treatment was statistically significantly lower in the first group that was started early, WBC, Neutrophil, Creatine, CK, CRP, D-Dimer, PCT, LDH. By collecting the data obtained as a result of the research, early deaths can be prevented worldwide. Our study recommending alternative treatment approaches is important for the protection of patients' quality of life. In this study, when all biochemical markers were evaluated together, it was evaluated that starting Favipiravir treatment early was beneficial in treating COVID-19 disease.